FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA GURU DI SEKOLAH DASAR KECAMATAN TELANAI PURA - Suhaila , Suhaila; Ahmad Husaini ,; Suroso , Suroso (Jurnal Cakrawala Ilmiah, 2025)
Work stress is a dynamic condition in which individuals face demands, opportunities, or resource constraints related to personal goals, where the outcome is uncertain but important. In Indonesia, work stress remains a occupational health issue, although comprehensive national data on the prevalence of work stress is not yet available. This study aims to identify factors associated with work stress among elementary school teachers in Telanaipura District. This study uses an analytical survey design with a cross-sectional approach, in which independent and dependent variables are measured simultaneously. Analysis was conducted to identify the relationship between workload, work environment, and other factors with the incidence of work stress among elementary school teachers. The results showed that 40 teachers (50%) experienced severe work stress, 74 teachers (87.1%) had a heavy workload, and 80 teachers (95.3%) worked in an unsupportive environment. Bivariate analysis found a relationship between workload (p=0.026) and environmental conditions (p=0.026) and the level of work stress among elementary school teachers. The Education Office is expected to conduct regular monitoring of teachers who are at risk of experiencing work stress due to workload or work environment, and to immediately intervene so that it does not affect their performance. In addition, positive programs are needed to improve the welfare of elementary school teachers